Practicality of popular scientific book on Odonata - Fadlhi Ashar Junaidi; Mochamad Arief Soendjoto; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The Popular Scientific Book (PSB) on Odonata that inhabits the Tabanio Coastal Forest, Tanah Laut Regency has been completed, but its practicality has yet to be determined. The aim of the research was to determine the practicality of the PSB. The determining parameters were readability, applicability, and student responses which in this case are undergraduate students of the Biology Education Study Program. Readability was tested by three students using the one-to-one method. The implementation was tested by five observers through a small group assessment (on five students using the PSB) to get the expected implementation value and field test assessment (on 10 students) so that the actual implementation was obtained. Student responses were obtained from small groups (five students) and field tests (10 students). The result is that the readability of the book is categorized as Very Good, the implementation of expectations and actual implementation is categorized as Very Good, as well as the expected and actual responses from students Strongly Agree. With these categories, this PSB on Odonata is stated to be practical to use.Abstrak Buku Ilmiah Populer (BIP) tentang Odonata yang menghuni Hutan Pantai Tabanio, Kabupaten Tanah Laut telah selesai, namun belum ditentukan kepraktisannya. Tujuan dari penelitian ini adalah untuk mengetahui kepraktisan BIP. Parameter yang menentukan adalah keterbacaan, penerapan, dan tanggapan mahasiswa yang dalam hal ini adalah mahasiswa S1 Program Studi Pendidikan Biologi. Keterbacaan diuji oleh tiga mahasiswa dengan menggunakan metode one-to-one. Implementasi diuji oleh lima orang pengamat melalui penilaian kelompok kecil (pada lima mahasiswa menggunakan BIP) untuk mendapatkan nilai implementasi yang diharapkan dan penilaian uji lapangan (pada 10 mahasiswa) sehingga diperoleh implementasi yang sebenarnya. Respon mahasiswa diperoleh dari kelompok kecil (lima mahasiswa) dan uji lapangan (10 mahasiswa). Hasilnya adalah keterbacaan buku dikategorikan Sangat Baik, pelaksanaan harapan dan pelaksanaan aktual dikategorikan Sangat Baik, serta respon yang diharapkan dan aktual dari mahasiswa Sangat Setuju. Dengan kategori tersebut, BIP di Odonata ini dinyatakan praktis untuk digunakan.